Bagi Hasil Usaha Pembibitan Tanaman Sistim Mertelu Dalam Perspektif Hukum Islam - Saifudin Saifudin; Waluyo Sudarmaji; Muhajir Muhajir (Indonesia, 2022)
The plant nursery business has become one of the livelihoods for the farming community in Sendangsari Village, Benar District, Purworejo Regency. The practice of muamalah with a profit-sharing cooperation model that has been running for decades has bright prospects due to the high market demand from year to year, which makes plant nursery activities grow rapidly. From that, various collaborations in plant nursery activities emerged, one of which was in the form of profit sharing. This study intends to describe the practice of profit-sharing cooperation between plant nursery farmers and landowners used to develop a nursery business. In addition, to find out how the contract that occurs in the profit-sharing cooperation in the perspective of Islamic law. This type of research is a field research (field research) with an analytical descriptive approach. The theory used to dissect this problem is profit sharing in the syirkah system with the conclusion that the practice of sharing the results of the plant seed business in Sendangsari Village is in accordance with Islamic law and has reflected the value of justice, because even though the manager's costs appear to be greater than the cash capital, the land owner will but the value of the land value contributed to the business is very expensive so it is worth it if the land value is considered one-third of the total accumulated assets.